PENGARUH PENGGUNAAN SUMBER DAYA AIR DAN JUMLAH HARI KERJA TERHADAP BIAYA ENERGI LISTRIK DI DINAS PUPR PERA PROVINSI KALIMANTAN TIMUR - Nazwa Aulia; Indra Maulana (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2026)
The purpose of this study is to analyze how water usage and the number of working days affect electricity costs at the Public Works and Public Housing Office (PUPR PERA) of East Kalimantan Province. Water usage and the number of working days were used as independent variables, while electricity cost was used as the dependent variable. This study uses multiple linear regression analysis. The results indicate that although electricity costs have a positive relationship with water usage and the number of working days, their effects are not significant at the 5% significance level. The main conclusion of this study is that electricity costs are more strongly influenced by the use of dominant electrical equipment, such as air conditioners, computers, and lighting. This study provides a new perspective by examining the relationship between office operational factors and energy consumption. The method provides a better understanding of the components affecting electricity costs in government offices. The findings suggest that energy management policies in government offices should place greater emphasis on the use of electrical equipment and energy efficiency. Future studies should identify other factors to identify other factors that may have a more significant influence on electricity costs